A 5-year longitudinal analysis of modifiable predictors for outdoor play and screen-time of 2- to 5-year-olds. Issue 1 (December 2016) - Xu, Huilan; Wen, Li; Hardy, Louise; Rissel, Chris
Abstract Background Early childhood is a critical time for establishing physical activity and sedentary behaviours. Identifying modifiable predictors of physical activity and sedentary behaviours in the early life stages can inform the development of early intervention programs. The aim of this study was to identify modifiable predictors of outdoor play (a proxy of physical activity) and screen-time in 2- to 5-year-olds. Methods A longitudinal data analysis was conducted using 5-year follow-up data from the Healthy Beginnings Trial undertaken in Sydney, Australia from 2007 to 2013. A total of 667 pregnant women were recruited for the study. Information on mothers' demographics, physical activity, screen-time, knowledge of child development, and awareness of childhood obesity during pregnancy (at baseline); children's tummy time (a colloquial term describing the time when a baby is placed on his or her stomach while awake and supervised) at 6 months old and screen-time at 1 year old was collected via interviews with participating mothers as potential modifiable predictors. Main outcomes were children's outdoor playtime and screen-time at ages 2, 3.5, and 5 years. Mixed linear and logistic regression models were built to determine these modifiable predictors. Results Mothers' screen-time during pregnancy (β = 2.1, 95 % CI 0.17–4.12;P  = 0.030) and children's daily screen-time at age 1 year (β = 15.2, 95 % CI 7.28–23.11;P  < 0.0001) predicted children's daily screen-time across ages 2 to 5 years after controlling for confounding factors. Practising tummy time daily (β = 13.4, 95 % CI 1.26–25.52;P  = 0.030), mother's physical activity level (β = 3.9, 95 % CI 0.46–7.28;P  = 0.026), and having been informed about playing with child at baseline (β = 11.6, 95 % CI 1.56–21.54;P  = 0.023) predicted children's outdoor playtime across ages 2 to 5 years. Conclusions Mothers played an important role in their children's outdoor play and screen-time in the first years of live. Children's early exposure to screen devices could be associated with their later screen-time. Early interventions to improve young children's physical activity and sedentary behaviour should focus on improving pregnant women's physical activity, awareness of playing with their child, reducing their own screen-time as well as practicing daily tummy time for infants after giving birth. Trial registration The Healthy Beginnings Trial is registered with the Australian Clinical Trial Registry (ACTRNO12607000168459 ). Registered 13 March 2007. Prospectively registered.